1994
DOI: 10.1007/bf00006520
|View full text |Cite
|
Sign up to set email alerts
|

Durations of development and production estimates by two crustacean zooplankton species Thermocyclops oblongatus Sars (Copepoda) and Diaphanosoma excisum Sars (Cladocera), in Lake Naivasha, Kenya

Abstract: Durations of embryonic and post-embryonic development of the two dominant zooplankton crustaceansThermocyclops oblongatus (Copepoda) and Diaphanosoma excisum in Lake Naivasha were determined at various lake water temperatures to provide the time element for the calculation of their production. Developmental times were temperature dependent in as much as food resource was not limiting. Production estimates were calculated. The turnover times of their biomass was 11.4 and 13.7 days, with production rates of 11.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…Bottrell, 1975b;Anderson & Benke, 1994;Anderson et al, 1998;Lemke, 2000). Egg development times of Diaphanosoma brachyurum in this study (8.4-2.0 days) were comparable with those reported for D. brachyurum reared at 21-22°C (2-2.3 days; Kotov & Boikova, 1998), and 10-25°C (11.4-1.4 days; Herzig, 1984), and were within the ranges reported by Mavuti (1994) for the tropical species, D. excisum, reared at 19°C (3.2 days) and 25°C (1.7 days). Similarly, egg development times were comparable between Simocephalus serrulatus reared at 15 and 20°C in this study (6.1 and 3.7 days, respectively) and S. vetulus reared at the same temperatures (6.1 and 3.9 days; Bottrell, 1975b).…”
Section: Growth and Reproduction Of Wetland Cladocerans 599supporting
confidence: 90%
See 1 more Smart Citation
“…Bottrell, 1975b;Anderson & Benke, 1994;Anderson et al, 1998;Lemke, 2000). Egg development times of Diaphanosoma brachyurum in this study (8.4-2.0 days) were comparable with those reported for D. brachyurum reared at 21-22°C (2-2.3 days; Kotov & Boikova, 1998), and 10-25°C (11.4-1.4 days; Herzig, 1984), and were within the ranges reported by Mavuti (1994) for the tropical species, D. excisum, reared at 19°C (3.2 days) and 25°C (1.7 days). Similarly, egg development times were comparable between Simocephalus serrulatus reared at 15 and 20°C in this study (6.1 and 3.7 days, respectively) and S. vetulus reared at the same temperatures (6.1 and 3.9 days; Bottrell, 1975b).…”
Section: Growth and Reproduction Of Wetland Cladocerans 599supporting
confidence: 90%
“…The functional role of zooplankton in terms of their secondary production and as energetic links between lower and higher trophic levels has been well documented in lakes (e.g. Culver & DeMott, 1978;Lim & Fernando, 1978;Lemly & Dimmick, 1982;Petersen, 1983;Forsyth & James, 1991;Mason & Abdul-Hussein, 1991;Mengestou & Fernando, 1991;Vuille, 1991;Mavuti, 1994). These studies have typically focused on pelagic species, although several investigators have reported the comparatively high production of microcrustaceans associated with vegetation within the lake littoral (Lim & Fernando, 1978;Vuille, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Some aspects, such as the structure of phytoplankton community or other food resources available (specially comparing environments within same trophic state), must be evaluated concomitantly with zooplankton productivity rates. Several estimates of secondary productivity of tropical zooplankton have been made for large African lakes (Burgis, 1974;Hart and Allanson, 1975;Mavuti, 1994). Despite the scarcity of similar studies in Brazilian aquatic ecosystems in past decades (Rocha and Matsumura-Tundisi, 1984), the number of studies has been growing (Maia-Barbosa, 2000;Peláez-Rodríguez, and Matsumura-Tundisi, 2002;2006;Rietzler et al, 2004;Santos-Wisniewski and Rocha, 2007;Panarelli et al, 2010;Santos et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…D. excisum is perennial in tropical lakes with water temperatures above 18.58C [e.g., Lake Naivasha, (Mavuti 1994), Lake Malawi (Irvine and Waya 1999)]. It has been collected in Hainan in January as well as April (Sinev et al 2015).…”
Section: Excisum Northern Range Limitmentioning
confidence: 99%